Evaluation of quality of pedagogic model for blended learning on course “Life safety” - M. V. Legan (Открытое образование (Москва))
The article is devoted to evaluating the quality of the pedagogical model for the students’ blended learning on the course «Health and Safety». A choice of the used technologies, forms, active and interactive methods in the learning process, learning tools is made; a new generation of multi-media resources is developed; the quality of teaching evaluation by blended learning model according to the process approach is carried out.The purpose of the study was to assess the quality blended learning model with different ratios of classroom and e-learning component of students on the course “Health and Safety”.Two groups of students were involved in the experiment:1st experimental group (152 persons) were the students of all areas of training, learning on the course “Health and Safety”, using a blended approach. E-learning technologies were used to provide the access to information resources (electronic educational-methodical complex on discipline, placed in the electronic educational environment of the University), the organization of self-study, sending the lecturer coursework and examinations, passing the intermediate and final testing for the purpose of monitoring assessment of the knowledge quality. This kind of blended learning models («with a web-enabled learning») is characterized by the addition of electronic educational resources without reducing the hours of a traditional component.2nd experimental group: (164 persons) – students enrolled in the course «Health and Safety» in the blended learning model. Students have been using the distance technology for self-study according to the curriculum – 80% of university hours. Personal communication («face to face») was with the lecturer during the session.We have tested two groups of students who participated in the experiment (final control) via a module testing electronic environment. In order to assess the quality of blended learning model we used a process approach. An effective questionnaire method was used for self-analysis of pedagogical activity. Some indicators for monitoring of opinions on the quality of the learning process for the blended model, designed in the form of a questionnaire, were identified.The pedagogical model of the blended learning course «Health and Safety» shows the structure of the pedagogical process: target, informative, organizational and activity, analytical and productive components.A choice of the used technologies, forms, active and interactive methods in the learning process, learning tools is made; a new generation of multi-media resources is developed; the quality of education according to the process approach is made; the results of the mastering of the course «Health and Safety» in the two groups of students are demonstrated.It is shown that the results of mastering of the course «Health and Safety» at different structural models of the blended learning are virtually identical. The successful mastering of the topic «Electrical Safety» requires the use of laboratory settings and simulators, as well as further study during the session in the classrooms. It is shown that a process approach, revealing the area for improvement, is applicable for making the self-assessment of the blended learning. We have received the high indicators of the quality training satisfaction for the blended model in both groups.The high level of satisfaction with the quality of e-learning environment and placed in its electronic resources promotes organizing of education in the remote access.